Enhancing Employee Engagement Through a Novel Mathematical Model in the Hospitality Sector of India - Chug, Pramod Kumar; Vibhuti, (Prabandhan: Indian Journal of Management, 2017)
The purpose of this study was to focus on employee's psychological resources by investigating the effects of organizational culture and communication and develop a mathematical model on the basis of the interrelationships which exist between them. This study explored the direct relationship between various factors of organization culture and communication such as autonomy, external orientation, inter departmental cooperation, human resource orientation, improvement orientation, organization integration, supervisory communication, personal feedback, corporate information, communication climate, co-worker communication, media quality, subordinate communication with employee engagement measured in terms of absorption, vigor, and dedication. Group method of data handling (GMDH) machine learning technique was used to measure, build, test, and validate the full structural comprehensive and non-linear complex relationships which existed among hospitality staff working in Delhi and NCR area. This study represented one of the first mathematical models of employee engagement, and an attempt was made to quantify the effectiveness of each of the organizational aspects on employee engagement discretely. Results provided insights into the weightage of each independent variable in maintaining an optimal organizational culture and communication to elevate the overall level of employee engagement. The results revealed that employees who got personal feedback, especially from their supervisors, had comparatively higher levels of employee engagement. Other important factors of organizational culture and communication, which comparatively carried more weightage are media quality, external orientation, human resource orientation, and organization orientation. The proposed mathematical model can be applied as a general framework to augment organizational culture and communication so as to achieve optimized employee engagement.